Application of IoT-Based System for Monitoring Energy Consumption - Ida Bagus Gede, Purwania; I Nyoman, Satya Kumara; Made, Sudarma (International Journal of Engineering and Emerging Technology; Vol 5 No 2 (2020): July - DecemberDO - 10.24843/IJEET.2020.v05.i02.p014, 2020)
Energy conditions in Indonesia are not balanced so there is an overlap between energy demand and availability. Energy demand will continue to increase with population and industry growth, but the availability of energy will continue to decrease. Uncontrolled energy consumption will certainly increase damage to the environment which in turn worsens global warming. Energy management is a best practice so that the use of energy is well managed. Technological developments can also support energy management by utilizing IoT technology. This study conducted a systematic literature review related to the application of IoT in energy management systems. The results of the literature review conducted are that IoT which was built for energy management consists of several components, such as microcontrollers, sensors, modules, communication protocols, and cloud-based systems. Microcontrollers often used in building IoT systems are Arduino and NodeMCU. The sensor is varies depending on the measurement requirements, usually using the current sensor and voltage sensor.